Stable COX17 downregulation leads to alterations in mitochondrial ultrastructure, decreased copper content and impaired cytochrome c oxidase biogenesis in HEK293 cells - Vanišová, Marie; Burská, Daniela; Spáčilová, Jana; Daňhelovská, Tereza; Dosoudilová, Žaneta; Zeman, Jiří; Stibůrek, Lukáš; Hansíková, Hana (Folia biologica (Praha), 2019)
Cox17 is an assembly factor that participates in early cytochrome c oxidase (COX, CcO) assembly stages. Cox17 shuttles copper ions from the cytosol to the mitochondria and, together with Sco1 and Sco2, provides copper ions to the Cox1 and Cox2 mitochondrially encoded subunits. In Saccharomyces cerevisiae, Cox17 also modulates mitochondrial membrane architecture due to the interaction of Cox17 with proteins of the MICOS complex (mitochondrial contact site and cristae organizing system). There is currently no data regarding the impact of long-term Cox17 deficiency in human cells. Here, we present construction and characterization of three stable COX17 shRNA-downregulated HEK293 cell lines that have less than 10 % of the residual Cox17 protein level. Cox17-depleted cell lines exhibited decreased intramitochondrial copper content, decreased CcO subunit levels (Cox1, Cox4 and Cox5a) and accumulation of CcO subcomplexes. Similarly to yeast cells, mitochondria in Cox17-downregulated HEK293 cell lines exhibited ultrastructural changes including cristae reduction and mitochondrial swelling. Characterization of the molecular pathogenesis of long-term Cox17 deficiency complements our knowledge of the mitochondrial copper metabolism and assembly of cytochrome c oxidase in human cells.
Keywords: transportéry mědi; HEK293 buňky; Copper; HEK293 Cells; RNA, Small Interfering; mitochondrie; lidé; Mitochondrial Proteins; respirační komplex IV; Copper Transport Proteins; Electron Transport Complex IV; malá interferující RNA; Mitochondria; mitochondriální proteiny; měď; Humans